Foxfire 6 : shoemaking, gourd banjos, and songbows, one hundred toys and games, wooden locks, a water powered sawmill, and other affairs of just plain living / edited, with an introd. by Eliot Wigginton. - Wigginton, Eliot.
Đầu trang nhan đề:Includes "Cumulative index for Foxfire 4, Foxfire 5 and Foxfire 6."